Exchange rates and fundamentals: new evidence from real-time data - Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2004)
This paper analyses the link between economic fundamentals and exchange rates by investigating the importance of real-time data. We find that such economic news in the United States, Germany and the euro area have indeed been a driving force behind daily US dollar – euro/DEM exchange rate developments in the period 1993-2003. The larger importance of US macroeconomic news is at least partly explained by their earlier release time compared to corresponding German and euro area news. The exchange rate is also shown to respond more strongly to news in periods of large market uncertainty and when negative or large shocks occur. Overall, the model based on real-time data is capable of explaining about 75% of the monthly directional changes of the US dollar-euro exchange rate, although it does not explain well the magnitude of the exchange rate changes.
Keywords: F31; F42; E52; 330; announcements; EMU; euro area; Exchange Rates; fundamentals; interdependence; news; real-time data; United States; US dollar euro